General practitioners' responsibilities to their patients. Issue 6645 (6th August 1988) - Whitfield, M.; Bucks, R.
Abstract : The views of general practitioners about their responsibilities for patient care have not been canvassed. A survey of general practitioners was therefore carried out to determine their views. A postal questionnaire, in which general practitioners were asked what they saw as their responsibilities, was sent to 525 principals in Avon and completed by 424, giving a response rate of 81%. The doctors generally agreed that their responsibilities for patient care included problems related to internal medicine, such as managing diabetes and hypertension. Less consensus was found in the replies to questions about technical procedures, such as resection of ingrowing toenails, and gynaecological, orthopaedic, or psychosocial problems. The results supported the view that general practitioners are gradually abandoning technical aspects of medicine to specialists without a compensating role having been defined. In the light of this trend the responsibilities of general practitioners should be clearly defined by the profession.